2005
DOI: 10.1902/jop.2005.76.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Coping With Stress: Its Influence on Periodontal Therapy

Abstract: The results of this study show that passive coping strategies were more pronounced in advanced disease as well as in cases of poor response to a non-surgical periodontal treatment, whereas patients with active coping modes had milder disease and a more favorable course of treatment. Thus, maladaptive behavior, especially in association with behavior-related risk factors such as smoking, are of great importance in the medical history, treatment, and maintenance of patients with periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…High levels of anxiety, stress, and depression affect patients' pain perception, their use of pain medication, and wound healing 8‐37 . The connection between the body and mind is a topic of much controversy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of anxiety, stress, and depression affect patients' pain perception, their use of pain medication, and wound healing 8‐37 . The connection between the body and mind is a topic of much controversy.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Rozlog et al, 22 patients experiencing stress were slower in their recovery from periodontal surgery compared to patients not experiencing stress. In addition, healing following periodontal surgery was impacted negatively by patients' inability to use effective coping mechanisms 23 . In 2004, Takada et al 24 showed that increased stress modulated the progression of periodontal inflammation.…”
Section: The Role Of Stress In Dentistrymentioning
confidence: 99%
“…It was found that supportive periodontal care was more effective in patients with aggressive periodontitis harboring less stress . A study to explain the influence of coping with stress on periodontal therapy concluded that patients with maladaptative coping strategies have more advanced disease and poor response to a nonsurgical periodontal treatment . A study was conducted to show the influence of emotional intelligence (a measure of the coping mechanisms) on the initial responses to periodontal treatment in patients with chronic periodontitis.…”
Section: Effect Of Stress On Wound Healingmentioning
confidence: 99%
“…Patients with maladaptive coping strategies have more advanced disease and poor response to non-surgical treatment,[35] whereas positive correlation was observed in reduction of dental plaque and gingival bleeding in patients having an active coping. [36] Furthermore, the cellular immune response plays a vital role in wound healing.…”
Section: Stress and Periodontal Diseasementioning
confidence: 99%